2021
DOI: 10.3390/molecules26133889
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Different Measurement Methods for Characterizing Rheological Properties of Lubrication Layer

Abstract: The lubrication layer plays a governing role in predicting the pumpability of fresh concrete. To determine the effect of measurement methods on the characterization of the rheological properties of the lubrication layer, different measurement systems, including Sliper, tribometer, and the utilization of a mortar rheometer, were employed. The rheological properties and workability of bulk concrete were measured in parallel to investigate the correlation between them and the rheological properties of the lubrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This feature suggested that increase of the MO SSA favored the heterogeneous nucleation, accelerating the cement paste hydration and consolidation reactions. This acceleration of the storage modulus highlights the potential of these MO-modified pastes for different applications, such as 3D printing of cementitious materials, since they can comply with the main processing requirements, including (i) adequate initial fluidity for shaping by pumping or extrusion, and (ii) accelerated paste consolidation, avoiding flow/deformation under the influence of gravity. , …”
Section: Resultsmentioning
confidence: 92%
“…This feature suggested that increase of the MO SSA favored the heterogeneous nucleation, accelerating the cement paste hydration and consolidation reactions. This acceleration of the storage modulus highlights the potential of these MO-modified pastes for different applications, such as 3D printing of cementitious materials, since they can comply with the main processing requirements, including (i) adequate initial fluidity for shaping by pumping or extrusion, and (ii) accelerated paste consolidation, avoiding flow/deformation under the influence of gravity. , …”
Section: Resultsmentioning
confidence: 92%